Fast Decoding of Images With Cryptcodes for Burst Channels - Popovska Mitrovikj, Aleksandra; Mechkaroska, Daniela; Bakeva, Verica (Institute of Electrical and Electronics Engineers (IEEE), 2023)
The concept of cryptcoding arises from the need to obtain secure and accurate transmission. This has led to an intensive development of coding theory and cryptography as scientific fields dealing with these problems. To ensure efficient and secure data transmission at the same time, the concept of cryptcoding is being developed, in which the coding and encryption processes are merged into one process. Cryptcodes provide correction of a certain number of errors in the transmitted message and data confidentiality, using only one algorithm. In this paper, we consider cryptcodes based on quasigroups, proposed elsewhere. Also, Burst-Cut-Decoding, Burst-4-Sets-Cut-Decoding, FastB-Cut-Decoding and FastB-4-Sets-Cut-Decoding algorithms for transmission of messages through burst channels have been defined and investigated elsewhere. Here, we investigate performances of these algorithms for transmission of images through burst channels. We made experiments for different channel parameters and compared the results obtained with different decoding algorithms of these cryptcodes. In all experiments, we considered the bit-error probability and the differences between the transmitted and decoded images. From the results presented in this paper we can conclude that Fast algorithms improve the performances of these cryptcodes for transmission of images over a burst channel. The best results are obtained by FastB-4-Sets-Cut-Decoding algorithm. In addition, to enhance the quality of the decoded images, we examined the application of a filter for visual correction of unsuccessfully decoded pixels using the surrounding pixels. The considered cryptcodes and presented results can be useful for application in satellite digital video broadcasting (DVB-S) coding and encryption schemes.
Keywords: Cryptcoding; error-correcting codes; burst channel; image; quasigroups